The Source a guide by subject to children's fiction, poetry and short stories from around the world with an emphasis on Australian books - White, Kerry; Turton, Rayma; Magpies Magazine Pty Ltd. (Grange, Qld. : Magpies Magazine Pty Ltd, 2000)
The Source is a searchable bibliographic database to children's literature by subject from around the world with an emphasis on Australian and New Zealand books. It has been published on the web to allow for continuous updating and is the result of many years of work by Kerry White in the bibliographical field of Australian children's literature, together with input and additions by the Magpies team and with suggestions and advice from Lyn Linning.
Description based on home page (viewed Jan. 29, 2003).
The source is continuously updated and is accessed by subscription.
Mode of access: Internet via World Wide Web.
System requirements: Computer or workstation with Internet access and graphical World Wide Web browser.
Keywords: Children's literature -- Bibliography -- Databases; Children's literature, Australian -- Bibliography -- Databases; Australian